Materials for Teaching Folklore and Literature of the Hutsul Region - Paska, Taras (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
Review of books: Igor Pelypeyko, Play. Knyha dlya chytannya pro Hutsul’shchynu, Hutsul’s’ka shkola, Yavoriv 1996, pp. 416. Igor Pelypeyko, Floyara. Khrestomatiya z hutsul’s’koho fol’kloru, Pysanyy Kamin’, Kosiv 1999, pp. 226.